30-minute website marketing : a step by step guide - Wilson, Lee (Bingley, UK : Emerald Publishing Limited, 2019)
Every high priority website marketing action can be distilled into a 30 minute time-frame. This practical guide provides step-by-step actions ready to implement, distilled from over 15 years of experience leading digital marketing departments.
Includes bibliographical references (pages 167-170) and index.
Keywords: Internet marketing; Internet advertising